IMPROVING READING COMPREHENSION AND SPEAKING ACHIEVEMENTS OF THE EIGHTH GRADERS OF SMP NEGERI 18 PALEMBANG THROUGH SHARED READING STRATEGY - ZANANDA, TIRAY FEBRIA (Sriwijaya University Learning and Education International Conference, 2016)
This study aimedat investigatingwhether or not the use of Shared Reading Strategy was effective to improve the studentsâ reading comprehension and speaking achievements. Quasi experimental research method was applied. The sample consisted of 44 eighth graders which were divided equally into experimental and control groups. The data were collected by using reading and speaking tests. Both groups were tested before and after the treatment. Using paired sample, the results of the experimental group showed that the two variables reading comprehension and speaking achievementssignificantly improved. Furthermore, the result of the independent t-test showed that the experimental group outperformed the control group with a significant mean difference of 9.545 (p=.000) on reading comprehension and 2.5000(p=.000) on speaking achievement. The results showed that the students who were taught by using Shared Reading Strategy had better improvement in their reading comprehension and speaking achievements. Thus, it can be concluded that Shared Reading Strategy could improve the studentsâ reading comprehension and speaking achievements.